Bronchiectasis and inhaled tobramycin: A literature review. (February 2022) - Elborn, J. Stuart; Blasi, Francesco; Haworth, Charles S.; Ballmann, Manfred; Tiddens, Harm A.W.M.; Murris-Espin, Marlène; Chalmers, James D.; Cantin, André M.
Abstract: Background: Inhaled antibiotics have been incorporated into contemporary European and British guidelines for bronchiectasis, yet no inhaled antibiotics have been approved in the United States or Europe for the treatment of bronchiectasis not related to cystic fibrosis. Pseudomonas aeruginosa infection is common in patients with bronchiectasis, contributing to a cycle of progressive inflammation, exacerbations, and airway remodelling. Objective: The aim of the current study was to identify and evaluate published studies of inhaled tobramycin solution or powder in patients with bronchiectasis and P. aeruginosa infection not associated with cystic fibrosis. Methods: A literature review was conducted utilising the PubMed and Cochrane databases. Studies published in the English language that reported safety and/or efficacy outcomes of inhaled tobramycin either alone or in combination with other antibiotics were included. Results: Seven clinical trials published between 1999 and 2021 were identified that met inclusion criteria. Inhaled tobramycin therapy was effective in reducing P. aeruginosa microbial density in the sputum of patients with bronchiectasis. Several studies demonstrated favourable impacts on hospitalisations, number and severity of exacerbations, and symptoms. Other studies were underpowered for these clinical outcomes or were exploratory in nature. Although tobramycin was generally well tolerated, some evidence of treatment-associated wheezing was reported. Conclusions: In patients with bronchiectasis and chronic P. aeruginosa infection, inhaled tobramycin was effective in reducing the density of bacteria in sputum, which may be associated with additional clinical benefits. Definitive phase 3 trials of inhaled tobramycin in patients with bronchiectasis are indicated to determine clinical efficacy and long-term safety. Highlights: This review examines 7 studies of inhaled tobramycin in bronchiectasis. Patients had Pseudomonas aeruginosa infection and no evidence of cystic fibrosis. Inhaled tobramycin therapy reduced microbial density of P. aeruginosa in sputum. Several studies showed a positive impact on clinical symptoms and hospitalisations. Phase 3 trials of inhaled tobramycin in patients with bronchiectasis are needed.